2019
DOI: 10.18332/tpc/111533
|View full text |Cite
|
Sign up to set email alerts
|

Insights on electronic cigarette products from reviews on the Reddit forum

Abstract: INTRODUCTION E-cigarette devices and their component parts are continuously evolving. Little is known about the product design features that may increase the appeal of e-cigarette use, ultimately affecting continuation of use. Product reviews have been described as useful in helping to forecast the popularity of products, and online reviews have become an important channel of product information. This study analyzed e-cigarette product reviews to attempt to arrive at a greater understanding of the features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…To the best of our knowledge, this is the first cross-platform semi-supervised attempt in tobacco research. (Allem et al, 2019;Carroll et al, 2012;Yanamandra et al, 2020;Zhang et al, 2018). While explored a thematic analysis of hookah Twitter posts, Allem et al (2017a) explored e-cigarette trends with an emphasis on social bot behaviour.…”
Section: Neutralmentioning
confidence: 99%
“…To the best of our knowledge, this is the first cross-platform semi-supervised attempt in tobacco research. (Allem et al, 2019;Carroll et al, 2012;Yanamandra et al, 2020;Zhang et al, 2018). While explored a thematic analysis of hookah Twitter posts, Allem et al (2017a) explored e-cigarette trends with an emphasis on social bot behaviour.…”
Section: Neutralmentioning
confidence: 99%
“…One analysis of Reddit threads indicated that primary motivations for vaping among individuals with mental illness include self-medication, freedom and control, vaping as a hobby, social connectedness, as well as vaping to quit smoking [ 32 ]. Other studies have used Reddit data to analyze public responses and concerns about vape bans [ 33 ], communities supporting e-cigarette cessation [ 34 ], and attitudes and reviews toward e-cigarette products [ 35 ].…”
Section: Introductionmentioning
confidence: 99%